Analisa Gaya Kepemimpinan, Motivasi, Budaya Kerja Mempengaruhi Kinerja Dan Dimediasi Komitmen Pada Rumah Sakit Jayakarta - Nia Puspita Hapsari; Endang Ruswanti (Jurnal Manajemen DIVERSIFIKASI, 2025)
The leadership style of a business venture is important for the sustainability and development of climate, and employee performance. The problems in hospitals seen from the pre-survey showed that leadership style is 69%, employee satisfaction is 59%, employee motivation is 55%, the culture planned by the organization is 60% implemented by employees, organizational commitment is 60% and employee performance is 62%. For this reason, this research will examine transformational leadership style, intrinsic motivation, organizational culture, employee commitment, and performance. The research method is surveyed and quantitative research. Data was collected through questionnaires to capture latent variables—sampling applied purposive sampling, namely employees who have worked for more than one year. The analysis tool used was SEM with the Lisrel program, the research sample was 157 respondents consisting of 87 women and 70 men aged 24-39 years. The research results imply that employee performance is mediated by commitment, commitment is influenced by leadership style, and leadership and organizational culture directly influence employee performance.